Trigeminal Neuralgia: Basic and Clinical Aspects - Araya, Erika I.; Claudino, Rafaela Franco; Piovesan, Elcio Juliato; Chichorro, Juliana Geremias (Current Neuropharmacology, 2020)
The trigeminal nerve is the largest of all cranial nerves. It has three branches that provide the main sensory innervation of the anterior two-thirds of the head and face. Trigeminal neuralgia (TN) is characterized by sudden, severe, brief, and stabbing recurrent episodes of facial pain in one or more branches of the trigeminal nerve. Pain attacks can occur spontaneously or can be triggered by non-noxious stimuli, such as talking, eating, washing the face, brushing teeth, shaving, a light touch or even a cool breeze. In addition to pain attacks, a proportion of the patients also experience persistent background pain, which along with autonomic signs and prolonged disease duration, represent predictors of worse treatment outcomes. It is now widely accepted that the presence of a neurovascular compression at the trigeminal root entry zone is an anatomic abnormality with a high correlation with classical TN. However, TN may be related to other etiologies, thus presenting different and/or additional features. Since the 1960s, the anticonvulsant carbamazepine is the drug of choice for TN treatment. Although anti-epileptic drugs are commonly used to treat neuropathic pain in general, the efficacy of carbamazepine has been largely limited to TN. Carbamazepine, however, is associated with dose-limiting side-effects, particularly with prolonged usage. Thus, a better understanding and new treatment options are urgently warranted for this rare, but excruciating disease.
Keywords: epidemiology